Neutralizing Antibody Response to the AreXvy Respiratory Syncytial Virus Vaccine in Lung Transplant Recipients: Assessment Against Reference and Seasonal Strains - Liran Levy; Dafna Yahav; Mark Benzimra; Yael Bezalel; Tomer Hoffman; Neta Shirin; Tomer Sinai; Menucha Jurkowicz; Ofir Deri; Noa Matalon; Milton Saute; Yaniv Lustig; et al. (Vaccines)
Background: Respiratory Syncytial Virus (RSV) is a significant cause of morbidity and mortality among lung transplant (LTx) recipients. Therapeutic options are limited, emphasizing the importance of prevention. The Arexvy® vaccine (RSVPreF3) showed promising efficacy among immunocompetent adults; however, data on its immunogenicity in solid organ transplant recipients remain unclear. Methods: A single-center retrospective cohort study, including all LTx recipients who were vaccinated with Arexvy in February 2024. Baseline and follow-up serum samples (1, 3, and 6 months post-vaccination) were analyzed for antibody responses using a commercial RSV ELISA kit and micro-neutralization assays against historical reference RSV A/B ATCC strains and seasonal RSV strains. Adverse events were documented. Results: A total of 28 recipients received the vaccine. Twenty-one (75%) were male, and the median age was 62 years (interquartile range [IQR], 53–67). The median time from transplant was 486 days (IQR, 243–966). Vaccination elicited strong immunogenic responses, demonstrating a twofold increase in ELISA-determined antibody levels at one month post-vaccination, which were sustained for six months. At one month, 67% of recipients had antibody levels exceeding the cutoff threshold. Micro-neutralization assays showed a significant increase in neutralizing antibodies against all tested variants (RSV A/B ATCC and seasonal RSV A/B), with titers remaining at least twofold higher than pre-vaccination levels. No serious adverse events were observed. Conclusions: Our findings demonstrate a sustained antibody response to the Arexvy® vaccine in a cohort of LTx recipients, with antibody titers sustained over six months. Further research is needed to assess the long-term durability of the immune response and the potential immunogenicity of this vaccine in LTx populations.